Detection of impact-produced dust clouds near the lunar terminator. (1st November 2019) - Berezhnoy, A.A.; Velikodsky, Yu.I.; Zubko, E.; Iten, M.; Lena, R.; Sposetti, S.; Tereshchenko, A.A.; Popel, S.I.; Feoktistova, E.A.; Golub', A.P.
Abstract: Analysis of observations of unique impact-produced flash near the lunar terminator was performed. Maximal brightness of detected thermal flash is 5.2–5.9 m in R band, mass of impacted meteoroid is about 0.18–28 kg. Height of shadow in the place of meteoroid's impact was only about 1 km, making it possible observations of impact-produced dust particles ejected to the lunar exosphere through their sunlight-scattering response. We detected two (fast and slow) clouds that were expanding with 3 km/s and 0.1 km/s, respectively. The maximal brightness reached by these fast and slow clouds in R band was 6.7 m and 10 m, respectively. Apparent mass of visible ejecta in fast and slow clouds is constrained to 80–8300 and 6–180 kg, respectively. Fast cloud consists of melt droplets and condensed grains while slow cloud consists of ejected lunar regolith dust particles. Highlights: Impact flash (about 5.5 m in R band) near the lunar terminator was detected. Two dust clouds ejected to the lunar exosphere upon impact were detected. Expansion velocity of fast and slow clouds is estimated to be 3 km/s and 0.1 km/s. Mass of micron-size particles in these clouds is constrained to about 1000 and 30 kg.